The Semantics and Evolution Mechanism of the Emerging Internet Catchphrase “X Men”: 新兴网络流行语“X门”的语义及演变机制探析 - Meng Lin (Mandarinable: Journal of Chinese Studies, 2025)
The catchphrase "X men" refers to a "faction" or its members composed of individuals who adore a particular entity, while simultaneously conveying the meaning of the loanword "amen" when used at the end of a sentence. Netizens employ "X men" to express their fervent enthusiasm for a given subject. The construction "X men" involves both the content and nature of "X" and "men," and its productivity has undergone significant modification, evolving from a monosemous to a polysemous expression. This series of semantic shifts is underpinned by cognitive operational mechanisms. Through the conceptual blending mechanism of radial development, the neologism "X men" emerges as a semantically coherent and functionally versatile structure, enabling its flexible application and subsequent proliferation in online discourse.